Multidimensional Governance For Islamic Philanthropic Institutions: Extended Maqashid Sharia Perspective - Mayasari, Rosalina Pebrica; Triyuwono, Iwan; Purwanti, Lilik; Andayani, Wuryan (Accounting Department, 2023)
Purpose — This study aims to build the concept of sharia governance of Islamic philanthropic institutions based on extended maqashid sharia. Design/methodology/approach — This research is qualitative research with a religionist paradigm rooted in Islamic values (Qur'an and Sunnah) and following sharia (maqashid sharia) objectives. The methodology built is an Islamic integrative methodology that integrates mashallah elements from the extended maqashid sharia. Findings — Multidimensional governance is intended to achieve Allah's pleasure in this world and the hereafter. Mashlahah (benefits) can be realized by maintaining the five dimensions of the extended maqashid sharia: spiritual, physical and non-physical, intellectual, social, and financial. Practical implications — This governance concept can be used to build new awareness for practitioners of Islamic philanthropic institutions or other Sharia nonprofit institutions in carrying out the idea of governance derived entirely from the Qur'an and hadith. The results of this study can also be used as a guide in improving the quality of governance of Islamic philanthropic institutions, leading to the increased trust of the people in Islamic philanthropic institutions. Originality/value—The concept of multidimensional governance is built from an intact reality. Multidimensional governance includes material, religious, Aaliyah, Kamiya, and messiah elements, as well as submission and obedience to Allah as the source of reality, knowledge, and truth so that the scope of governance is intact, covering material and non-material matters in addition to the aims and objectives of the world and hereafter. Paper type — case study